Pemanfaatan Satwa Sebagai Obat Tradisional Dalam Upaya Peningkatan Kajian Etnozoologi di Desa Pangkalniur dan Berbura - HERI, HERI; Syafutra, Randi; Putri Dalimunthe, Nurzaidah; Priyansah, Sujadi; Hendra Bayu, Hendi (CONSERVA, 2024)
Pangkalniur Village and Berbura Village are two of several villages that surround the Gunung Maras National Park. Since ancient times, people in these two villages have fulfilled their living needs by utilizing the natural resources around the mountain. One of the natural resources that is often used by the people of Pangkalniur Village and Berbura Village is the wild animals that live around the Mount Maras National Park area. These animals are usually used as traditional medicine. This research aims to determine the use of wild animals as traditional medicine by the people in Pangkalniur Village and Berbura Village, as well as knowing the types and parts of animals used, methods and management of animals as traditional medicine, as well as the properties and conservation status of animals used as traditional medicine. This research was conducted from March 2024 to June 2024. The method used was snowball sampling which included a preliminary survey and determining informants, then collecting primary data through interviews. Based on the results of interviews, 12 families and 13 species were obtained which were grouped into 6 classes, namely Reptilia, Mammalia, Actinopterygii, Insecta, Clitellata, Aves, and Amphibia.